Edukasi Tentang Verbal Bullying pada Siswa Kelas XI di SMK Soedirman Purbalingga: Penelitian - Imanda, Harisma Aulia; Triana, Noor Yunida; Cahyaningrum, Etika Dewi (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Adolescence is a transitional period between childhood and adulthood. One form of violence that frequently occurs in educational settings is verbal bullying, which involves intimidation through words that hurt others. Data from the National Center for Educational Statistics shows a rate of 1 in 5 (20.8%). Verbal bullying is also a focus of international organizations such as Plan International–ICRW in five Asian countries: Vietnam (79%), Cambodia (73%), Nepal (79%), Pakistan (43%), and Indonesia (84%). In Purbalingga, data from the Regional Technical Implementation Unit (UPTD) shows an increase in cases from 44 to 56 reports since 2021, so health education about verbal bullying for adolescents is essential to increase student knowledge. Education is provided through lectures, discussions, questions and answers, and media such as leaflets, posters, and PowerPoint presentations. Pre-test results showed that 4 students had sufficient knowledge (13%) and 26 had good knowledge (87%). After education, all 30 adolescents (100%) were categorized as having good knowledge, with an average score increasing from 87.63 to 96.46, an increase of 8.33%. It is hoped that further research will further examine the factors causing verbal bullying in educational settings. The author plans to publish the results of the Community Service Program (PKM) in a national journal.